Identification of Five Sibling Species of the Anopheles barbirostris complex (Diptera: Culicidae) in Thailand by a Polymerase Chain Reaction Assay - Suwannamit, Sittiporn (Asian Health, Science and Technology Reports, 2021)
Anopheles barbirostris is a complex of six sibling species that are almost identical in adult morphology. The lack of accurate identification method, diagnosis based on only adult morphological characters has led to misidentification. This complex has been incriminated, as malaria and filarial vector in Indonesia and Thailand but knowledge of the epidemiology and vectorial roles of this species group are poorly known. For this purpose, a diagnostic PCR system to differentiate among five sibling species of the An. barbirostris species complex in Thailand was developed by using two PCR reactions. Based on nucleotide differences in the ITS2 sequences, novel degenerate primer was constructed for amplification in combination with a universal reverse primer to generate amplification products of specific length for each of species. The first PCR reaction can identify An. barbirostris species complex in four species, i.e., An. dissidens, An. saeungae, An. barbirostris species A3, and An. barbirostris s.s. by using universal primer pairs and the second PCR reaction can distinguish species An. barbirostris s.s. from An. wejchoochotei by using new primer and universal reverse primer. Additionally, An. saeungae can be clearly differentiated on PCR product from An. barbirostris s.s. and An. wejchoochotei by using new primer.